Visit to Blue Earth Village - Ritterbush, Lauren W. (My University, 2015)
For more than four centuries the Kanza (Kaw) Indians made their homes in what we now recognize as part of the state of Kansas. Early during this period they lived along the Missouri River, but traveled widely, including along the river that bears their name, the Kansas or Kaw River. By the late eighteenth century they had established a permanent village (or villages) along the Kansas. Here they experienced both continuity and change as the cultural and political dynamics of the region shifted with more frequent and intense contact, direct and indirect, with Euroamericans. Clues to the experiences of the Kanzas in the early nineteenth century can be extracted from the written records produced by some of those who visited and through limited archaeological investigations of their former homes. This article provides a glimpse of Kanza life through the eyes of others, particularly a party of the Long Expedition of 1819. This view reveals a period of relative quiescence before the dramatic changes in Kanza society following the Treaty of St. Louis in 1825.
Citation: Ritterbush, L. (2015). Visit to Blue Earth Village. Kansas History, 38(1). http://www.kshs.org/publicat/history/2015spring_ritterbush.pdf
Keywords: Kanza Indian (Native American) tribe; Blue Earth Village; Major Stephen H. Long; Long Expedition; Native Americans in Kansas; Thomas Say